Father Nurturance as Moderators of Perceived Family Support for College Students’ Entrepreneurial Intentions - Ersa Lanang Sanjaya; Dewi Retno Suminar; Nur Ainy Fardana (Psychosophia: Journal of Psychology, Religion, and Humanity, 2021)
The main objective of this study is to examine the role of family support in the entrepreneurial intentions of college students, particularly the role of fathers. Understanding entrepreneurial intentions in the context of college students are imperative to encouraging future entrepreneurial behaviors. Family support is an important external factor in predicting college students’ entrepreneurial intentions. Another aspect of family support that must be considered is the unique role of father nurturance, specifically, in relation to college students’ entrepreneurial intentions. The respondents consisted of 189 college students between the ages of 18 and 25 years studying in Surabaya. The study utilized quantitative and correlational approaches with data analyzed using regression. The main data collection tool used in the study was a questionnaire. The research findings show that family support has a significant positive influence on entrepreneurial intentions in college students. Father nurturance is a moderating variable that strengthens the influence of family support and entrepreneurial intentions on college students. The implication of this research is to highlight the importance of the family’s role in supporting the entrepreneurial process. In addition, fathers, specifically, play a unique role as supporters and positive role models in increasing the entrepreneurial intentions of college students.